Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Significant crust-thinning beneath the Ilan Plain of Taiwan for revealing westward impingement of the Okinawa Trough opening into Taiwan Orogeny - Ya-Chuan Lai; Cheng-Horng Lin; Min-Hung Shih; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Tectonophysics, 2026)

Uncovering an aseismic slab for showing the flipping of subduction polarity in the Taiwan area - Lin Cheng-Horng; Min-Hung Shih; Ya-Chuan Lai; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Journal of Asian Earth Sciences, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Association between air pollution and obstructive sleep apnea in terms of respiratory event frequency and lung-to-finger circulation time - Rachel Chien; Zhihe Chen; Peizheng Wang; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Arnab Majumdar; Jiunn-Horng Kang; Kang-Yun Lee; Wun-Hao Cheng; Yi-Chih Lin; Cheng-Jung Wu; et al. (Atmospheric Pollution Research, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Efficient fluoride recovery from wastewater using mesoporous Ca-based nanomaterials derived from municipal solid waste incineration fly ash via fluidized bed crystallization - Cheng-Kuo Tsai; Nur Atirah Afifah Sezali; Zhi-Fu Lin; Jao-Jia Horng; Hui Lin Ong (Journal of Environmental Chemical Engineering, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Investigation of ammonia-induced lethal toxicity toward ion regulation in zebrafish embryos - Li-Yih Lin; Chieh-An Cheng; Sian-Tai Liu; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Machine learning approaches for rice crop yield predictions using time-series satellite data in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Horng-Yuh Guo; Youg-Sing Cheng; Shu-Ling Chen; Huan-Sheng Lin; Shih-Hsiang Chen (International Journal of Remote Sensing, 2020)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Three-dimensional shallow velocity structure beneath Taal Volcano, Philippines - Shuei-Huei You; Konstantinos I. Konstantinou; Yuancheng Gung; Cheng-Horng Lin (Journal of Seismology, 2017)

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes - Chia-Ron Yang; Kao-Shang Shih; Jing-Ping Liou; Yi-Wen Wu; I-Ni Hsieh; Hsueh-Yun Lee; Tzu-Cheng Lin; Jyh-Horng Wang (Journal of Molecular Medicine, 2014)

A low-pH medium in vitro or the environment within a macrophage decreases the transcriptional levels of fimA, fimZ and lrp in Salmonella enterica serovar Typhimurium - Ke-Chuan Wang; Yuan-Hsun Hsu; Yi-Ning Huang; Ter-Hsin Chen; Jiunn-Horng Lin; Shih-Ling Hsuan; Maw-Sheng Chien; Wei-Cheng Lee; Kuang-Sheng Yeh (Journal of Biosciences, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Geomagnetic anomaly at Lunping before the 1999 Chi-Chi earthquake (M w = 7.6) in Taiwan - Kuang-Jung Chen; Bonbbon Chiu; Jee-Shiang Wang; Cheng-Yu Lee; Cheng-Horng Lin; Kevin Chao (Natural Hazards, 2011)

Characteristics of Atmospheric Aerosol and Acidic Gases from Urban and Forest Sites in Central Taiwan - Man-Ting Cheng; Chuen-Liang Horng; Yu-Chi Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)